2022
DOI: 10.22271/j.ento.2022.v10.i1a.8920
|View full text |Cite
|
Sign up to set email alerts
|

Potentiality of some botanical extracts as biopesticides against the maize weevil, Sitophilus zeamais Motsch. (Coleoptera: Curculionidae)

Abstract: Laboratory studies were conducted with the aim of investigating the efficacy of some botanicals in the management of Sitophilus zeamais Motsch infesting stored sorghum. The selected plant species were Euphorbia balsamifera Aiton, Lawsonia inermis L. and Mitracarpus hirtus L. Chloroform leaf extracts of the botanicals applied at 6.25, 12.50, 25.00, 50.00 and 100.00 mgml -1 were applied to determine their effect on adult survival, concentration of total body protein and inhibition of acetycholinesterase enzyme (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Therefore, the use of plant materials as bio-pesticides for the control of insect pests has been considered as an indigenous pest management for reducing damage caused by pests [46,47,48] . The botanicals can be used in various forms such as powders, extracts of different organic solvents, essential oils or as dried whole plants applied as layers in between grains in traditional stores [24,35,49,50,51,52,53,54] . Researchers have been engaged in testing insecticidal activities of different plant species against the maize weevils infesting cereal grains in Nigerian stores.…”
Section: Control Of Sitophilus Zeamais Using Botanical Productsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the use of plant materials as bio-pesticides for the control of insect pests has been considered as an indigenous pest management for reducing damage caused by pests [46,47,48] . The botanicals can be used in various forms such as powders, extracts of different organic solvents, essential oils or as dried whole plants applied as layers in between grains in traditional stores [24,35,49,50,51,52,53,54] . Researchers have been engaged in testing insecticidal activities of different plant species against the maize weevils infesting cereal grains in Nigerian stores.…”
Section: Control Of Sitophilus Zeamais Using Botanical Productsmentioning
confidence: 99%
“…There have been a lot of research efforts to investigate the potentiality of plant materials on adult mortality of S. zeamais in stored cereal grains [33,35,40,42,43,54,55,56,57,59,60,73] . It was also confirmed that some botanical extracts resulted in promising adult mortality of maize weevil in Nigeria.…”
Section: Toxicity Potential Of Plant Products Against Sitophilus Zeamaismentioning
confidence: 99%
See 1 more Smart Citation